«Русская речь в ее крестьянском варианте». Заметки о прозе Федора Абрамова(“Russian language in its peasant form”. Notes on F. Abramov's prose) - Lönngren, Tamara (Poljarnyj vestnik, 1998)
This article deals with the problem of the use of dialect in literary prose. The work chosen for analysis is F. Abramov's novel «Dom» (‘The house'). F. Abramov (1920-1983) was born and grew up near the river Pinega in the Archangel'sk oblast'. Up to the age of 14 his only language was the Pinega dialect. After that he studied and worked in Leningrad. He came to master the literary language, but constantly visited his home village of Verkola and was eager not to lose contact with its inhabitants and their language. In his prose there are many features of the Pinega dialect.In this article, special attention is paid to vocabulary. There are about 200 dialect words in Abramov's novel. Some of them are used very frequently, such as robit' ‘work', kažinnyj ‘every', dak ‘so', pošto ‘why', none ‘now', žorat' ‘eat, drink', odneždy ‘once', kalit' ‘scold', etc.Many dialect words are used together with their literary counter- parts. This creates the doublets so typical of contemporary dialects, for example dom / khoromy ‘house', dvor / zaulok ‘yard', gornica / gostinaja ‘living-room'. Here the semantic group "Buildings" is singled out for closer investigation.In the life of the village nicknames play an important role. The 28 nicknames found in the novel are analyzed and commented on from the point of view of Russian folk culture.
Keywords: Russian; language; dialectology; Fedor Abramov